A Note on the Semi-Inverse Method and a Variational Principle for the Generalized KdV-mKdV Equation - Li Yao; Yun-Jie Yang; Xing-Wei Zhou (Abstract and Applied Analysis)
Ji-Huan He systematically studied the inverse problem of calculus of variations. This note reveals that the semi-inverse method also works for a generalized KdV-mKdV equation with nonlinear terms of any orders.